Micro-activities for Java programming learning - Tchutchulashvili, Mariami (2016)
This work aims to study new ways of contributing to minimize the great difficulty that students have shown in the first programming disciplines of computer courses. It is difficult for a beginner to structure the thinking in order to achieve complete mapping between the problem to be solved and the program (code) that solves. A great capacity of abstraction is needed and for that the use of views can help the student to understand the algorithm to be implemented. It is also important to improve the autonomous capacity for problem solving and make the student more independent. This thesis is based on the construction of WebQuest in order to test a motivating strategy for Java programming learning and check if this kind of learning methodology is good and efficient. So, in this thesis a WebQuest for Java programming is implemented and tested in classroom context.